Tectonism of Late Noachian Mars: Surface Signatures from the Southern Highlands - Trishit Ruj; Goro Komatsu; Gene Schmidt; Suniti Karunatillake; Kenji Kawai (Remote Sensing, 2022)
Upwelling mantle plumes often instigate extensional stress within the continental crust of Earth. When stress exceeds crustal strength, extensional structures develop, reducing the effective stress and trigger magmatic processes at the crust–mantle boundary. However, such processes and their relationship to the formation of many surface structures remain poorly characterized on Mars. We identified a series of extensional structures in the southern highlands of Mars which collectively resemble continental rift zones on Earth. We further characterized these extensional structures and their surrounding region (area of ~1.8 M km2) by determining the surface mineralogy and bulk regional geochemistry of the terrain. In turn, this constrains their formation and yields a framework for their comparison with extensional structures on Earth. These terrains are notable for olivine and high-Ca pyroxene with a high abundance of potassium and calcium akin to alkali basalts. In the case of Mars, this Earth-like proto-plate tectonic scenario may be related to the plume-induced crustal stretching and considering their distribution and temporal relationship with the Hellas basin, we conclude that the plume is impact-induced. Overall, the findings of this work support the presence of mantle plume activity in the Noachian, as suggested by thermal evolution models of Mars.